DIFFERENCES IN THE FORMATION OF SOCIAL RESPONSIBILITY OF COLLECTIVES IN SPECIFIC ORGANIZATIONS - Кирьян, Елена; Дюженко, Михаил; Замора, Сергей (SWorldJournal, 2020)
The paper considers the content of social responsibility of business entities. The generalized attitude of ordinary citizens and the majority of managers and administrations to social responsibility is noted. In order to focus on the need to consider the